The case for an advisory center on international investment law - Umirdinov Alisher (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Taking the success story of the Advisory Center on WTO Law in providing subsidized, low-cost legal advice to developing and LDC members of the World Trade Organization, investment law researchers should ask whether we need a similar advisory center in the field of international investment arbitration.
Keywords: 330